An Organic Spin Valve Embedding a Self‐Assembled Monolayer of Organic Radicals. Issue 14 (6th May 2016) - Poggini, Lorenzo; Cucinotta, Giuseppe; Pradipto, Abdul‐Muizz; Scarrozza, Marco; Barone, Paolo; Caneschi, Andrea; Graziosi, Patrizio; Calbucci, Marco; Cecchini, Raimondo; Dediu, Valentin Alek; Picozzi, Silvia; Mannini, Matteo; et al.
Abstract : A novel functionalization of a ferromagnetic electrode employed in spintronic devices is reported. Self‐assembling monolayer technique has been used to chemisorb a paramagnetic phosphonate functionalized nitronyl‐nitroxide radical (NitPO) on the ferromagnetic La0.7 Sr0.3 MnO3 (LSMO) manganite surface. This interfacial layer causes clearly detectable modifications of the behavior in prototypical LSMO/NitPO/Gaq3 /AlO x /Co vertical spintronic devices at temperatures below the ferromagnetic alignment (estimated by density functional theory) of the magnetic moments of NitPO and LSMO. This behavior can be justified by a significant spin filtering effect at the engineered interface, with a carrier selection (spin‐up) opposite to that of the LSMO/Gaq3 interface (spin‐down). It is proposed that the engineering of spin injecting interfaces with molecules having magnetic moment enables additional mechanisms to control and manipulate the spin polarization of currents in spintronic devices. Abstract : Self‐assembling of monolayer is used to include a nitronyl‐nitroxide radical in organic spin‐valves, demonstrating that the presence of the molecular paramagnetic layer does not hamper the observation of a significant magnetoresistance that is altered by a spin filtering exerted by this engineered spinterface.